Paradigms of Protist/Bacteria Symbioses Affecting Human Health: Acanthamoeba species and Trichomonas vaginalis - Henriquez, Fiona L.; Mooney, Ronnie; Bandel, Timothy; Giammarini, Elisa; Zeroual, Mohammed; Fiori, Pier Luigi; Margarita, Valentina; Rappelli, Paola; Dessì, Daniele (Frontiers in Microbiology, 2021)
Ever since the publication of the seminal paper by Lynn Margulis in 1967 proposing the theory of the endosymbiotic origin of organelles, the study of the symbiotic relationships between unicellular eukaryotes and prokaryotes has received ever-growing attention by microbiologists and evolutionists alike. While the evolutionary significance of the endosymbiotic associations within protists has emerged and is intensively studied, the impact of these relationships on human health has been seldom taken into account. Microbial endosymbioses involving human eukaryotic pathogens are not common, and the sexually transmitted obligate parasite Trichomonas vaginalis and the free-living opportunistic pathogen Acanthamoeba represent two unique cases in this regard, to date. The reasons of this peculiarity for T. vaginalis and Acanthamoeba may be due to their lifestyles, characterized by bacteria-rich environments. However, this characteristic does not fully explain the reason why no bacterial endosymbiont has yet been detected in unicellular eukaryotic human pathogens other than in T. vaginalis and Acanthamoeba, albeit sparse and poorly investigated examples of morphological identification of bacteria-like microorganisms associated with Giardia and Entamoeba were reported in the past. In this review article we will present the body of experimental evidences revealing the profound effects of these examples of protist/bacteria symbiosis on the pathogenesis of the microbial species involved, and ultimately their impact on human health.